2016
DOI: 10.2147/cia.s107626
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pedometer use and goal setting on walking and functional status in overweight adults with multimorbidity: a crossover clinical trial

Abstract: BackgroundWalking can improve functional status, and a pedometer and goal setting can increase walking and, potentially, gait speed. The efficacy of pedometer use and goal setting for increasing step counts among overweight and obese adults with multiple comorbid conditions has not been evaluated.MethodsWe recruited and randomly assigned obese or overweight adults with multimorbidity to immediate pedometer use with goal setting or delayed pedometer use, using a crossover design. The primary outcome of interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 35 publications
1
49
2
Order By: Relevance
“…Thus, patients who had <5000 steps at the midway measurement point were likely to continue to have <5000 steps. We did not observe an association between the length of pedometer wearing time and the status of <5000 steps at 4 months, an observation consistent with the original trial findings 14. A self-rated physical QoL score <50 had higher odds of <5000 steps at 4 months (adjusted OR 6.21, 95% CI: 2.32–18.54).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Thus, patients who had <5000 steps at the midway measurement point were likely to continue to have <5000 steps. We did not observe an association between the length of pedometer wearing time and the status of <5000 steps at 4 months, an observation consistent with the original trial findings 14. A self-rated physical QoL score <50 had higher odds of <5000 steps at 4 months (adjusted OR 6.21, 95% CI: 2.32–18.54).…”
Section: Resultssupporting
confidence: 86%
“…Focus on physical activity and sedentary behaviors or physical activity components alone showed only modest reductions in sedentary time. Pedometer use with SMART goals did not affect step status in our clinical trial 14. Age >65 years, BMI >35 kg/m 2 , and waist circumference >102 cm were also associated with <5000 steps at 4 months.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…A systematic review including 8 randomised controlled trials and 18 observational studies found that the usage of a pedometer is related to significant increases in physical activity and significant decreases by 3.8 mm Hg in SBP in a middle-aged population 18. The usage of a pedometer, setting a step goal and the use of a step diary may be key motivational factors for increasing physical activity 18 20. Pedometer users who were given a goal, whether it was the 10 000-step goal or an alternative personalised step goal, significantly increased their physical activity over baseline 21.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in physical functioning following physical activity interventions have been observed in multimorbidity [ 26 ]. However, few trials have looked at the effectiveness of interventions designed to improve lifestyle outcomes in patients with multimorbidity in primary care [ 27 ], and the evidence related to changes in lifestyle behaviours such as diet and physical activity is conflicting [ 28 30 ]. This observational and interventional evidence, across multiple outcomes and conditions, suggests that physical activity can be conceptualised as a composite marker of overall health status.…”
Section: Introductionmentioning
confidence: 99%